One Year Reinfection Rate of Hepatitis C Among Patients on Maintenance Hemodialysis After Successful Antiviral Treatment - Khurshid, Sanaa; Cheema, Sidra Shafiq; Cheema, Shafeeq (Pakistan Journal of Kidney Diseases, 2021)
Background: Direct acting antiviral therapies (DAA) are an important tool for hepatitis C virus elimination. Cross-contamination as a result of failure to follow infection control procedures. We estimated HCV reinfection rates among treated individuals on maintenance hemodialysis (MHD) in our dialysis patients. Methods: We analyzed data from Jinnah hospital dialysis center cohort on maintenance hemodialysis who previously took direct acting antiviral therapy (DAA) for treatment of hepatitis C in a prospective randomized interventional trial which included 36 patients. These patients were followed for one year after sustained virologic response (SVR) was achieved. At one year, reinfection was defined as a positive HCV RNA measurement at one year after achievement of SVR. Genotype was also assessed for patients who had positive HCV RNA by PCR. As a secondary objective, one year mortality was also calculated in this treated population. Results: Of 32 patients who were treated with DAAs, SVR after one year of completion of treatment was 100% in group 1 and 85.8% in group 2. None of the patients in group 1 had reinfection one year after achieving SVR while 2 out of 14 patients in group 2 were found to have reinfection with same genotype as previous. Overall reinfection rate was 2/32 (6.25%). Crude reinfection rate per 100 person-years was 6.25. One year mortality was 16% and 44% in group 1 and 2 respectively. Conclusion: Reinfection rate is low among successfully treated HCV patients on maintenance hemodialysis when strict implementation and adherence to ‘universal precautions’ is practiced.